The use and ethics of dental photography and social media at an oral healthcare training centre in South Africa - Faheema Kimmie-Dhansay; Nicoline Potgieter; Nanayaa Mprah; Lindeka Msane; Shaza Mowzer; Azraa Mowzer; Nosipho Mthupha; Tamiya Safodien; Mirriam Sindani; Jade Smith; Olwethu Solombela; Zahraa Suliman (AOSIS, 2024)
Background: The ethics surrounding the use and sharing of photographs on social media has come under the spotlight as the Protection of Personal Information Act (POPI Act) has come into play. Aim: The aim is to determine the use, ethical practice and sharing of dental photography on social media among qualified and undergraduate oral health practitioners at a dental school in South Africa. Methods: A cross-sectional study design was used on staff and students at the University of the Western Cape's Dental Faculty in 2022. Chi-squared and Fisher's exact tests were used to determine associations between the different graduation statuses and various demographic factors. Results: From the 80 undergraduate students and 46 qualified oral healthcare practitioners, the majority were aware that photography could be used in dentistry, and 87.3% (n = 110) took photographs of the dental treatments performed on their patients. Only 60.3% of the participants attended an ethical course that addressed issues with social media and digital photography. Almost 80% (n = 100) of the participants did not feel that they needed to mention all the social media platforms that they would use with their patients' photographs before sharing. Conclusion: Dental photography is being used and sometimes shared on social media platforms by some students and staff at university level. Not all participants have attended an ethical course on clinical photography. Dental training needs to include an ethical course on dental photography and the use of sharing photographs on social media. Contribution: Good ethical practice regarding clinical photographs in all undergraduate and postgraduate curriculums, to eliminate any uncertainty.